2006
DOI: 10.1111/j.1541-1338.2006.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Which Bets Paid Off? Early Findings on the Impact of Private Management and K‐8 Conversion Reforms on the Achievement of Philadelphia Students

Abstract: This article reports initial findings from a study of middle grades educational reforms in Philadelphia. We use multilevel change models to analyze the impact on student mathematics achievement of privatization through the use of educational management organizations (EMOs), taking account of the structural reforms (creation of new K-8 schools to replace selected middle schools) occurring simultaneously within the district. Overall, the longitudinal mathematics achievement gains for students in EMO-managed scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…First, it is not clear that simply shifting all schools to these two models will necessarily produce the effects found here. In particular, conversions of existing schools to these spans may take time to show positive effects (Mac Iver & Mac Iver, 2006).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is not clear that simply shifting all schools to these two models will necessarily produce the effects found here. In particular, conversions of existing schools to these spans may take time to show positive effects (Mac Iver & Mac Iver, 2006).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…For example, Bedard and Do (2005), using national data for 1987 to 1994, concluded that middle schools (Grades 6-8) were associated with lower on-time high school graduation rates. Mac Iver and Mac Iver (2006) and Byrnes and Ruby (2007) found evidence in Philadelphia that students in older K-8 schools, but not in recently converted schools, outperformed those in middle schools, although these older K-8 schools generally served a more advantaged student population.…”
mentioning
confidence: 99%
“…Philadelphia's example could be best characterized as a restart approach focusing on state takeover of schools with governance and management turned over to external operators. Researchers found that these schools did not outperform the gains compared with other schools within Philadelphia (Gill, Zimmer, Christman, & Blanc, 2007;MacIver & MacIver, 2006) despite the additional resources these schools were provided. 1 It is worth noting certain restrictions were placed on schools concerning what reforms they could implement, including a restriction to maintain the schools as neighborhood schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Government Accountability Office, 2012;Zollers & Ramanathan, 1998). A number of studies indicate that students in profit-oriented EMO charter schools have mixed, or often worse, academic growth (Byrnes, 2009;Educational Policy Institute, 2005;Garcia, Molnar, & Barber, 2009;Gill, Zimmer, Christman, & Blanc, 2007;M. A. Mac Iver & Mac Iver, 2006;Miron, 2008;U.S.…”
Section: Introductionmentioning
confidence: 99%